2014
DOI: 10.14429/dsj.64.7332
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Microstructural Studies on PVA/Co Nanocomposite Prepared by Ion Beam Sputtering Technique

Abstract: In this paper, we report the embedment of Cobalt (Co) nanoparticles by ion beam sputtering (IBS) in poly(vinyl alcohol) (PVA) substrate to prepare nanocomposite film. The Co film of 5 nm was deposited on PVA by IBS technique. Formation of nanocrystalline Co with hcp phase is revealed in GIXRD pattern of the film which also indicates that there is no change in the crystalline structure of PVA even after sputtering of the metallic nanoparticles. The average particle size of Co nanoparticles as evaluated using Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
(42 reference statements)
4
10
0
Order By: Relevance
“…In recent past we developed nanocomposite systems like PVA/Co, PVA/Co/C, and PVA/Co/Ag by sputtering nanoparticles of cobalt, carbon, and silver on PVA film where we found XRD peak in all such PVA/Co, PVA/Co/C, and PVA/Co/Ag systems in the same position at 2 θ = 19.81° as in the present pristine PVA film. It is worthy to note that the peak at 2 θ = 19.81° has maintained its stubborn presence and identity in each of such nanocomposite as PVA / Co, PVA / Co / C, and PVA / Co / Ag systems irrespective of sputtering pattern and sequence .…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…In recent past we developed nanocomposite systems like PVA/Co, PVA/Co/C, and PVA/Co/Ag by sputtering nanoparticles of cobalt, carbon, and silver on PVA film where we found XRD peak in all such PVA/Co, PVA/Co/C, and PVA/Co/Ag systems in the same position at 2 θ = 19.81° as in the present pristine PVA film. It is worthy to note that the peak at 2 θ = 19.81° has maintained its stubborn presence and identity in each of such nanocomposite as PVA / Co, PVA / Co / C, and PVA / Co / Ag systems irrespective of sputtering pattern and sequence .…”
Section: Resultssupporting
confidence: 52%
“…The interest for polymers is established from the fact that they can afford to generate wide range of tailored properties in presence of additives [4][5][6][7][8]. Polyvinyl alcohol (PVA) is one among the numerous polymers known today.…”
Section: Introductionmentioning
confidence: 99%
“…Banerjee et al [22] filled PVA with MnCl2 and obtained sunflower-like assembled pattern and a n value around 1.70 at 589 nm. Other studies were focused on doping PVA to display specific dielectric or magnetic characteristics [23][24][25][26]. One of the main advantages of PVA-based materials resides in the facile processing into components for optical devices, such as optical waveguides and optical image storage system [22].…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki and Lisfi 1-2 reported study on Co NPs embedded in PI (polyamide) and PET (Polyethylene Terephthalate). studies on Co embedded in PVA has been reported by our group earlier [3][4][5] which shows that PVA protects Cobalt (Co) from oxidation and the nanocomposite shows good magnetic property.The versatility and dependability of polyvinyl alcohol (PVA) polymer is established from the fact that they have attractive properties like lightweight, good mechanical and optical properties. Polyvinyl alcohol is also considered to be a good host material where dopants can modify its physiochemical properties.…”
Section: Introductionmentioning
confidence: 83%